Clinical effectiveness of an individually tailored strengthening programme, including progressive resistance exercises and advice, compared to usual care for ambulant adolescents with spastic cerebral palsy (ROBUST trial): a parallel group randomized controlled trial - Sally Hopewell; David J. Keene; Ioana Marian; Daniel C. Perry; Ines Rombach; Morag Andrew; Catherine Barry; Loretta Davis; Gregory Firth; Heidi Fletcher; Beth Fordham; Vivi Gregory Osborne; et al. (Bone & Joint Open)
Aims: Muscle strengthening exercises are one of the interventions frequently prescribed by physiotherapists for adolescents with cerebral palsy (CP). However, there is wide variability in the exercise regimes used and limited evidence of their effectiveness. The ROBUST trial will assess the clinical effectiveness of an individually tailored strengthening programme, including progressive resistance exercises and advice, compared to usual care for ambulant adolescents with spastic CP. Methods: We are conducting a multicentre, two-arm, parallel group, superiority randomized controlled trial. We will recruit adolescents aged 12 to 18 years with a diagnosis of spastic CP (bilateral or unilateral) Gross Motor Function Classification System (GMFCS) levels I to III who are able to comply with the assessment procedures and exercise programme with or without support. Participants will be recruited from at least 12 UK NHS Trust physiotherapy and related services. Participants (n = 334) will be randomized (centralized computer-generated 1:1 allocation ratio) to either: 1) a progressive resistance exercise programme, with six one-to-one physiotherapy sessions over 16 weeks; or 2) usual NHS care, with a single physiotherapy session and an assessment session, and advice regarding self-management and exercise. Conclusion: The primary outcome is functional mobility measured using the child-/parent-reported Gait Outcomes Assessment List (GOAL) at six months. Secondary outcomes are: clinician-assessed muscle strength (Five Times Sit-to-Stand Test) and motor function (timed up and go test) at six months; functional mobility (GOAL) at 12 months; independence (GOAL subdomain A), balance (GOAL subdomain A, B, D), pain and discomfort (GOAL subdomain C), health-related quality of life (youth version of the EuroQol five-dimension questionnaire; EQ-5D-Y), educational attendance, exercise adherence, and additional physiotherapy treatment (six and 12 months). The primary analysis will be intention to treat. Cite this article: Bone Jt Open 2025;6(5):517–527.